Strategi Manajemen Sekuriti Untuk Meningkatkan Kepercayaan Pengguna Terhadap Transaksi E-Wallet - Artha Bangkit Auliano; Filemon Leonardo Dongoran; Mohammad Diandra Ferdiansyah; Rasyid Darusman; Sandy Fitriansyah (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Abstract: Implementing a security management strategy is essential to ensure the security of electronic transactions, particularly in the use of digital wallets. E-wallets have become one of the most popular solutions for conducting online transactions, but they are often vulnerable to cyber-attacks and identity theft. This paper aims to examine security management strategies and practices that can be used to strengthen user protection in e-wallet transactions. The methods applied include literature review and data collection to identify security threats often faced by e-wallet users and mitigation measures that can be taken to reduce these risks. The strategies discussed include data encryption, double authentication, suspicious transaction monitoring, and user training on digital security practices. It is expected that the understanding and implementation of these security management practices will provide better protection for e-wallet users and increase their confidence in utilizing electronic transaction services.